3HWC: The Third HAWC Catalog of Very-high-energy Gamma-Ray Sources - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Solares, H. A. Ayala; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; et al. (Astrophysical Journal, 2020)
We present a new catalog of TeV gamma-ray sources using 1523 days of data from the High-Altitude Water Cherenkov (HAWC) Observatory. The catalog represents the most sensitive survey of the northern gamma-ray sky at energies above several TeV, with three times the exposure compared to the previous HAWC catalog, 2HWC. We report 65 sources detected at >= 5 sigma significance, along with the positions and spectral fits for each source. The catalog contains eight sources that have no counterpart in the 2HWC catalog, but are within 1 degrees of previously detected TeV emitters, and 20 sources that are more than 1 degrees away from any previously detected TeV source. Of these 20 new sources, 14 have a potential counterpart in the fourth Fermi Large Area Telescope catalog of gamma-ray sources. We also explore potential associations of 3HWC sources with pulsars in the Australia Telescope National Facility (ATNF) pulsar catalog and supernova remnants in the Galactic supernova remnant catalog.
CRIS-Team WoS Importer:2021-01-01

A deep spectromorphological study of the γ -ray emission surrounding the young massive stellar cluster Westerlund 1 - Aharonian, F.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Becherini, Y.; Berge, D.; Bi, B.; Böttcher, Markus; De Lavergne, M. De Bony; Bradascio, F.; Brose, R.; Brun, F.; et al. (Astronomy & Astrophysics, 2022)
Context. Young massive stellar clusters are extreme environments and potentially provide the means for efficient particle acceleration. Indeed, they are increasingly considered as being responsible for a significant fraction of cosmic rays (CRs) that are accelerated within the Milky Way. Westerlund 1, the most massive known young stellar cluster in our Galaxy, is a prime candidate for studying this hypothesis. While the very-high-energy γ-ray source HESS J1646-458 has been detected in the vicinity of Westerlund 1 in the past, its association could not be firmly identified. Aims. We aim to identify the physical processes responsible for the γ-ray emission around Westerlund 1 and thus to understand the role of massive stellar clusters in the acceleration of Galactic CRs better. Methods. Using 164 h of data recorded with the High Energy Stereoscopic System (H.E.S.S.), we carried out a deep spectromorphological study of the γ-ray emission of HESS J1646-458. We furthermore employed H I and CO observations of the region to infer the presence of gas that could serve as target material for interactions of accelerated CRs. Results. We detected large-scale ( 2 diameter) γ-ray emission with a complex morphology, exhibiting a shell-like structure and showing no significant variation with γ-ray energy. The combined energy spectrum of the emission extends to several tens of TeV, and it is uniform across the entire source region. We did not find a clear correlation of the γ-ray emission with gas clouds as identified through H I and CO observations. Conclusions. We conclude that, of the known objects within the region, only Westerlund 1 can explain the majority of the γ-ray emission. Several CR acceleration sites and mechanisms are conceivable and discussed in detail. While it seems clear that Westerlund 1 acts as a powerful particle accelerator, no firm conclusions on the contribution of massive stellar clusters to the flux of Galactic CRs in general can be drawn at this point.
CRIS-Team Scopus Importer:2022-11-11
Keywords: Acceleration of particles; Galaxies: star clusters: individual: Westerlund 1; Gamma rays: general; Radiation mechanisms: non-thermal; Shock waves; Stars: massive

A GeV to TeV view of shell-type SNRs - Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Baghmanyan, V.; et al. (Proceedings of Science, 2022)
Shock acceleration by the shells of supernova remnants (SNRs) has been hypothesized to be the mechanism that produces the bulk of Galactic Cosmic Rays, possibly up to PeV energies. Some SNRs have been shown to accelerate cosmic rays to TeV energies and above. But which SNRs are indeed efficient accelerators of protons and nuclei? And what is the maximum energy up to which they can efficiently accelerate particles? Measurements of non-thermal emission, especially in the gamma-ray regime, are essential to answer these questions. The High-Altitude Water Cherenkov (HAWC) observatory, surveying the northern TeV gamma-ray sky, is currently the most sensitive wide field-of-view survey instrument in the VHE (very-high-energy, >100 GeV) range and has recorded more than five years of data. The Large Area Telescope (LAT) onboard the Fermi satellite has been surveying the GeV gamma-ray sky for more than ten years. Combining measurements from both instruments allows the study of gamma-ray emission from SNRs over many orders of magnitude in energy. In this presentation, I will show measurements of VHE gamma-ray emission from Fermi-LAT-detected SNRs with the HAWC Observatory.
CRIS-Team Scopus Importer:2024-12-16

Air shower reconstruction using HAWC and the Outrigger array - Joshi, Vikas; Schoorlemmer, Harm (Proceedings of Science, 2019)
The High Altitude Water Cherenkov (HAWC) gamma-ray observatory detects cosmic- and gamma-ray initiated air showers in the TeV energy range using 300 water Cherenkov detectors (WCDs). To improve its sensitivity at the highest energies, HAWC has been upgraded with a sparse array of 345 small WCDs (outrigger array) around the HAWC main array. The outrigger array increases the instrumented area of HAWC by a factor of 4 and has started taking data since August 2018. A new gamma-ray reconstruction method has been developed to improve the reconstruction of the air showers which combines the data of mixed type particle detector arrays. In this contribution, we will show the first results of the combined air shower reconstruction of HAWC and its outrigger array using Monte Carlo simulations and the first combined experimental data set.
CRIS-Team Scopus Importer:2021-04-20

A MeerKAT, e-MERLIN, HESS, and Swift search for persistent and transient emission associated with three localized FRBs - Chibueze, J. O.; Caleb, M.; Spitler, L.; Ashkar, H.; Schüssler, F.; Stappers, B. W.; Venter, C.; Heywood,; Richards, A. M. S.; Williams, D. R. A.; Kramer, M.; Beswick, R.; et al. (Monthly Notices of the Royal Astronomical Society, 2022)
We report on a search for persistent radio emission from the one-off fast radio burst (11(B) 20190714A, as well as from two repeating FRBs, 20190711A and 20171019A, using the MeerKAT radio telescope. For FRB 20171019A, we also conducted simultaneous observations with the High-Energy Stereoscopic System (H.E.S.S.) in very high-energy gamma rays and searched for signals in the ultraviolet, optical, and X-ray bands. For this FRB, we obtain a UV flux upper limit of 1.39 x 10(-16) erg cm(-2) s(-1) angstrom(-1), X-ray limit of similar to 6.6 x 10(-14) erg cm(-2) s(-1) and a limit on the very high energy gamma-ray flux Phi(E > 120 GeV) < 1.7 x 10(-12) erg cm(-2) S-1. We obtain a radio upper limit of similar to 15 mu Jy beam(-1) for persistent emission at the locations of both FRBs 20190711A and 20171019A with MeerKAT. However, we detected an almost unresolved (ratio of integrated flux to peak flux is similar to 1.7 beam) radio emission, where the synthesized beam size was similar to 8 arcsec size with a peak brightness of similar to 53 mu Jy beam(-1) at MeerKAT and similar to 86 mu Jy beam(-1) at e-MERLIN, possibly associated with FRB 20190714A at z = 0.2365. This represents the first detection of persistent continuum radio emission potentially associated with a (as-yet) non- repeating FRB. If the association is confirmed, one of the strongest remaining distinction between repeaters and non-repeaters would no longer be applicable. A parallel search for repeat bursts from these FRBs revealed no new detections down to a fluence of 0.08 Jy ms for a 1 ms duration burst.
CRIS-Team WoS Importer:2022-08-05

An optimized search for dark matter in the galactic halo with HAWC - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistrán, T.; Carramiñana, A.; Casanova, S.; Chaparro-Amaro, O.; et al. (Journal of Cosmology and Astroparticle Physics, 2023)
The Galactic Halo is a key target for indirect dark matter detection. The High Altitude Water Cherenkov (HAWC) observatory is a high-energy (∼300 GeV to >100 TeV) gamma-ray detector located in central Mexico. HAWC operates via the water Cherenkov technique and has both a wide field of view of ∼ 2 sr and a >95% duty cycle, making it ideal for analyses of highly extended sources. We made use of these properties of HAWC and a new background-estimation technique optimized for extended sources to probe a large region of the Galactic Halo for dark matter signals. With this approach, we set improved constraints on dark matter annihilation and decay between masses of 10 and 100 TeV. Due to the large spatial extent of the HAWC field of view, these constraints are robust against uncertainties in the Galactic dark matter spatial profile.
CRIS-Team Scopus Importer:2024-12-16
Keywords: cosmic ray experiments; dark matter detectors; dark matter experiments; gamma ray experiments

Application of graph networks to background rejection in Imaging Air Cherenkov Telescopes - Glombitza, Jonas; Joshi, Vikas; Bruno, Benedetta; Funk, Stefan (Journal of Cosmology and Astroparticle Physics, 2023)
Imaging Air Cherenkov Telescopes (IACTs) are essential to ground-based observations of gamma rays in the GeV to TeV regime. One particular challenge of ground-based gamma-ray astronomy is an effective rejection of the hadronic background. We propose a new deep-learning-based algorithm for classifying images measured using single or multiple Imaging Air Cherenkov Telescopes. We interpret the detected images as a collection of triggered sensors that can be represented by graphs and analyzed by graph convolutional networks. For images cleaned of the light from the night sky, this allows for an efficient algorithm design that bypasses the challenge of sparse images in deep learning approaches based on computer vision techniques such as convolutional neural networks. We investigate different graph network architectures and find a promising performance with improvements to previous machine-learning and deep-learning-based methods.
CRIS-Team Scopus Importer:2023-12-01
Keywords: cosmic rays detectors; gamma ray detectors; Machine learning

Application of graph networks to γ/hadron separation in IACT image analyses - Glombitza, Jonas; Joshi, Vikas; Bruno, Benedetta; Funk, Stefan (Proceedings of Science, 2024)
Imaging Atmospheric Cherenkov Telescopes (IACTs) enable precise ground-based observations of the gamma-ray sky by imaging the distribution of Cherenkov light emitted during the development of air showers. Nowadays, many reconstruction algorithms rely on an elliptical high-level parameterization of these IACT images — the Hillas parameterization — and exploit their correlations. To overcome the limitations of the elliptical modeling, besides sophisticated analytical or template-based models, the advent of deep learning allows for reconstruction techniques that showed first promising results. By interpreting the detected images as a collection of triggered sensors that graphs can represent, we propose an algorithm based on graph networks for stereoscopic IACT image analyses. For images cleaned from background noise, this allows for an efficient algorithm design that bypasses the challenge of sparse images that occur in deep learning approaches based on convolutional neural networks. We investigate graph network architectures to two different stereoscopic data sets, simulated for the H.E.S.S. experiment. The algorithm enables an excellent γ/hadron separation with improvements to classical machine learning. Further, we find that the algorithm offers promising prospects for stereoscopic reconstructions also for telescopes featuring different camera geometries.
CRIS-Team Scopus Importer:2025-02-04

A search for spectral hardening in HAWC sources above 56 TeV - Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Baghmanyan, V.; et al. (Proceedings of Science, 2022)
The High Altitude Water Cherenkov (HAWC) Observatory is a wide-field-of-view gamma-ray observatory that is optimized to detect gamma rays between 300 GeV and several hundred TeV. The HAWC Collaboration recently released their third source catalog (3HWC), which contains 65 sources. One of these sources, the ultra-high-energy gamma-ray source 3HWC J1908+063, may exhibit a hardening of the spectral index at the highest energies (above 56 TeV). At least two populations of particles are needed to satisfactorily explain the highest energy emission. This second component could be leptonic or hadronic in origin. If it is hadronic in origin, it would imply the presence of protons with energies up to ∼1 PeV near the source. We have searched other 3HWC sources for the presence of this spectral hardening feature. If observed, this would imply that the sources could make good PeVatron candidates.
CRIS-Team Scopus Importer:2024-12-16

A Survey of Active Galaxies at TeV Photon Energies with the HAWC Gamma-Ray Observatory - Albert, A.; Alvarez, C.; Camacho, J. R. Angeles; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Solares, H. A. Ayala; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; Caballero-Mora, K. S.; et al. (Astrophysical Journal, 2021)
The High Altitude Water Cherenkov (HAWC) Gamma-Ray Observatory continuously detects TeV photons and particles within its large field of view, accumulating every day a deeper exposure of two-thirds of the sky. We analyzed 1523 days of HAWC live data acquired over four and a half years, in a follow-up analysis of 138 nearby (z < 0.3) active galactic nuclei from the Third Catalog of Hard Fermi-LAT sources culminating within 40 degrees of the zenith at Sierra Negra, the HAWC site. This search for persistent TeV emission used a maximum-likelihood analysis assuming intrinsic power-law spectra attenuated by pair production of gamma-ray photons with the extragalactic background light. HAWC clearly detects persistent emission from Mkn 421 and Mkn 501, the two brightest blazars in the TeV sky, at 65 sigma and 17 sigma level, respectively. Marginal evidence, just above the 3 sigma level, was found for three other known very high-energy emitters: the radio galaxy M87 and the BL Lac objects VER J0521+211 and 1ES 1215+303, the latter two at z similar to 0.1. We find a 4.2 sigma evidence for collective emission from the set of 30 previously reported very high-energy sources, with Mkn 421 and Mkn 501 excluded. Upper limits are presented for the sample under the power-law assumption and in the predefined (0.5-2.0), (2.0-8.0), and (8.0-32.0) TeV energy intervals.
CRIS-Team WoS Importer:2021-03-05

Characterizing γ-ray sources with HAL (HAWC Accelerated Likelihood) and 3ML - Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Baghmanyan, V.; et al. (Proceedings of Science, 2022)
The open-source Multi-Mission Maximum likelihood (3ML) Framework allows for the common analysis of diverse datasets. The ability to consistently fit and characterize astronomical data across many decades in energy is key to understanding the origin of the emission we measure with many different instruments. 3ML uses plugins to encapsulate the interfaces to data and instrument response functions. The user can then define a model with one or multiple sources to describe a given region of interest. The model is fit to the data to determine the locations, spatial shapes, and energy spectra of the sources in the model. The High Altitude Water Cherenkov (HAWC) Observatory, a wide FoV instrument sensitive to energies from 300 GeV to above 100 TeV, has used 3ML for data analysis for several years using a plugin optimized for single source analysis. As multisource fitting became more common, a faster plugin was required. Spectral fits to the Crab Nebula and the nearby source HAWC J0543+233 obtained using HAL, the HAWC plugin for 3ML, will be presented.
CRIS-Team Scopus Importer:2024-12-16

Constraining the local burst rate density of primordial black holes with HAWC - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Solares, H. A.Ayala; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; Caballero-Mora, K. S.; et al. (Journal of Cosmology and Astroparticle Physics, 2020)
Primordial Black Holes (PBHs) may have been created by density fluctuations in the early Universe and could be as massive as > 109 solar masses or as small as the Planck mass. It has been postulated that a black hole has a temperature inversely-proportional to its mass and will thermally emit all species of fundamental particles via Hawking Radiation. PBHs with initial masses of ∼ 5 × 1014 g (approximately one gigaton) should be expiring today with bursts of high-energy gamma radiation in the GeV-TeV energy range. The High Altitude Water Cherenkov (HAWC) Observatory is sensitive to gamma rays with energies of ∼300 GeV to past 100 TeV, which corresponds to the high end of the PBH burst spectrum. With its large instantaneous field-of-view of ∼ 2 sr and a duty cycle over 95%, the HAWC Observatory is well suited to perform an all-sky search for PBH bursts. We conducted a search using 959 days of HAWC data and exclude the local PBH burst rate density above 3400 pc-3 yr-1 at 99% confidence, the strongest limit on the local PBH burst rate density from any existing electromagnetic measurement.
CRIS-Team Scopus Importer:2020-05-22

Constraining the TeV Halo Population in M31 - Andrés, A.; Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistrán, T.; Yun-Cárcamo, S.; et al. (Proceedings of Science, 2024)
TeV halos are a new class of γ-ray sources recently observed around some middle-aged pulsars. They are extended γ-ray emission regions with a size bigger than the Pulsar Wind Nebulae but smaller than a Supernova Remnant. Several studies indicate that a TeV halo may be a general signature around a middle-aged pulsar, but this is still an open question. Some recent results suggest TeV halos are significantly contributing to the TeV emission of our Galaxy, and models have been proposed to reproduce the observed population of TeV halos in the Milky Way. In this work, we analyze the emission at TeV energies of the Andromeda galaxy (M31), the closest spiral galaxy to Earth. M31 has also been observed to have a GeV excess similar to the observed in the Galactic Center of our Galaxy. The aim of this work is to model the γ-ray emission at TeV energies in M31 assuming both the Milky Way and M31 share similar properties. Using 6 years of HAWC observations, we compute the flux upper limits in the region of M31 at TeV energies.
CRIS-Team Scopus Importer:2025-02-04

Constraints on Lorentz Invariance Violation from HAWC Observations of Gamma Rays above 100 TeV - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Solares, H. A. Ayala; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; et al. (Physical Review Letters, 2020)
Because of the high energies and long distances to the sources, astrophysical observations provide a unique opportunity to test possible signatures of Lorentz invariance violation (LIV). Superluminal LIV enables the decay of photons at high energy. The high altitude water Cherenkov (HAWC) observatory is among the most sensitive gamma-ray instruments currently operating above 10 TeV. HAWC finds evidence of 100 TeV photon emission from at least four astrophysical sources. These observations exclude, for the strongest of the limits set, the LIV energy scale to 2.2 x 10(31) eV, over 1800 times the Planck energy and an improvement of 1 to 2 orders of magnitude over previous limits.
CRIS-Team WoS Importer:2020-04-14

Constraints on the Intergalactic Magnetic Field Using Fermi-LAT and H.E.S.S. Blazar Observations - Aharonian, F.; Aschersleben, J.; Backes, M.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bi, B.; Bouyahiaoui, M.; Breuhaus, M.; Brose, R.; Brun, F.; et al. (Astrophysical Journal Letters, 2023)

Cosmic-ray energy reconstruction using machine learning techniques - Alvarado, A.; Capistrán, T.; Torres, I.; Sacahuí, J. R.; Alfaro, R.; Albert, A.; Alvarez, C.; Andrés, A.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; et al. (Proceedings of Science, 2024)
HAWC is a ground-based observatory consisting of 300 water Cherenkov detectors, which observes the extensive air showers induced by cosmic rays from some TeV to a few PeV and, in particular, gamma rays from 300 GeV to more than 100 TeV. One of the crucial features required for a detector of extensive air showers is the estimation of the primary energy of the events to study the spectra of cosmic and gamma rays. For HAWC there are currently two gamma-ray energy estimators: one relies on a ground density parameter, while the other utilizes an artificial neural network. For the cosmic ray energy estimation, there is only one estimator based on maximum likelihood procedures and measurements of the lateral charge distribution of the events. It is worthwhile to update the cosmic-ray energy estimator due to recent improvements of the extensive air shower offline-reconstruction techniques in HAWC. Therefore, we implemented an artificial neural network to reconstruct the primary energy of hadronic events trained with several observables that characterize the air showers. We trained several models and evaluated their performance against the existing cosmic ray energy estimator. In this work, we present the features and performance of these models.
CRIS-Team Scopus Importer:2025-02-04

Cosmic ray spectrum of protons plus helium nuclei between 6 and 158 TeV from HAWC data - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Belmont-Moreno, E.; Brisbois, C.; Caballero-Mora, K. S.; Capistrán, T.; et al. (Physical Review D, 2022)
A measurement with high statistics of the differential energy spectrum of light elements in cosmic rays, in particular, of primary H plus He nuclei, is reported. The spectrum is presented in the energy range from 6 to 158 TeV per nucleus. Data was collected with the High Altitude Water Cherenkov (HAWC) Observatory between June 2015 and June 2019. The analysis was based on a Bayesian unfolding procedure, which was applied on a subsample of vertical HAWC data that was enriched to 82% of events induced by light nuclei. To achieve the mass separation, a cut on the lateral age of air shower data was set guided by predictions of CORSIKA/QGSJET-II-04 simulations. The measured spectrum is consistent with a broken power-law spectrum and shows a kneelike feature at around E=24.0-3.1+3.6 TeV, with a spectral index γ=-2.51±0.02 before the break and with γ=-2.83±0.02 above it. The feature has a statistical significance of 4.1σ. Within systematic uncertainties, the significance of the spectral break is 0.8σ.
CRIS-Team Scopus Importer:2022-05-06

Detailed Analysis of the TeV γ-Ray Sources 3HWC J1928+178, 3HWC J1930+188, and the New Source HAWC J1932+192 - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velazquez, J. C.; Rojas, D. Avila; Solares, H. A. Ayala; Babu, R.; Belmont-Moreno, E.; Brisbois, C.; Caballero-Mora, K. S.; Capistran, T.; Carraminana, A.; et al. (Astrophysical Journal, 2023)
The latest High Altitude Water Cherenkov (HAWC) point-like source catalog up to 56 TeV reported the detection of two sources in the region of the Galactic plane at galactic longitude 52° < ℓ < 55°, 3HWC J1930+188 and 3HWC J1928+178. The first one is associated with a known TeV source, the supernova remnant SNR G054.1+00.3. It was discovered by one of the currently operating Imaging Atmospheric Cherenkov Telescope (IACT), the Very Energetic Radiation Imaging Telescope Array System (VERITAS), detected by the High Energy Stereoscopic System (H.E.S.S), and identified as a composite SNR. However, the source 3HWC J1928+178, discovered by HAWC and coincident with the pulsar PSR J1928+1746, was not detected by any IACT despite their long exposure on the region, until a recent new analysis of H.E.S.S. data was able to confirm it. Moreover, no X-ray counterpart has been detected from this pulsar. We present a multicomponent fit of this region using the latest HAWC data. This reveals an additional new source, HAWC J1932+192, which is potentially associated with the pulsar PSR J1932+1916, whose γ-ray emission could come from the acceleration of particles in its pulsar wind nebula. In the case of 3HWC J1928+178, several possible explanations are explored, in an attempt to unveil the origins of the very-high-energy γ-ray emission.
CRIS-Team Scopus Importer:2023-03-17

Detection of extended γ -ray emission around the Geminga pulsar with H.E.S.S. - Aharonian, F.; Ait Benkhali, F.; Aschersleben, J.; Ashkar, H.; Backes, M.; Barbosa Martins, V.; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlöhr, K.; Bi, B.; Böttcher, M.; et al. (Astronomy & Astrophysics, 2023)
Geminga is an enigmatic radio-quiet γ-ray pulsar located at a mere 250 pc distance from Earth. Extended very-high-energy γ-ray emission around the pulsar was discovered by Milagro and later confirmed by HAWC, which are both water Cherenkov detector-based experiments. However, evidence for the Geminga pulsar wind nebula in gamma rays has long evaded detection by imaging atmospheric Cherenkov telescopes (IACTs) despite targeted observations. The detection of γ-ray emission on angular scales ≳2° poses a considerable challenge for the background estimation in IACT data analysis. With recent developments in understanding the complementary background estimation techniques of water Cherenkov and atmospheric Cherenkov instruments, the H.E.S.S. IACT array can now confirm the detection of highly extended γ-ray emission around the Geminga pulsar with a radius of at least 3° in the energy range 0.5-40 TeV. We find no indications for statistically significant asymmetries or energy-dependent morphology. A flux normalisation of (2.8 ± 0.7)×10-12 cm-2 s-1 TeV-1 at 1 TeV is obtained within a 1° radius region around the pulsar. To investigate the particle transport within the halo of energetic leptons around the pulsar, we fitted an electron diffusion model to the data. The normalisation of the diffusion coefficient obtained of D0 = 7.6-1.2+1.5×1027 cm2 s-1, at an electron energy of 100 TeV, is compatible with values previously reported for the pulsar halo around Geminga, which is considerably below the Galactic average.
CRIS-Team Scopus Importer:2023-06-16
Keywords: Acceleration of particles; Diffusion; Gamma rays: general; Pulsars: general

Detection of very-high-energy γ -ray emission from the colliding wind binary η Car with H.E.S.S. - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; et al. (Astronomy & Astrophysics, 2020)
Aims. Colliding wind binary systems have long been suspected to be high-energy (HE; 100 MeV < E < 100 GeV) γ-ray emitters. η Car is the most prominent member of this object class and is confirmed to emit phase-locked HE γ rays from hundreds of MeV to 100 GeV energies. This work aims to search for and characterise the very-high-energy (VHE; E >100 GeV) γ-ray emission from η Car around the last periastron passage in 2014 with the ground-based High Energy Stereoscopic System (H.E.S.S.). Methods. The region around η Car was observed with H.E.S.S. between orbital phase p = 0.78-1.10, with a closer sampling at p ≈ 0.95 and p ≈ 1.10 (assuming a period of 2023 days). Optimised hardware settings as well as adjustments to the data reduction, reconstruction, and signal selection were needed to suppress and take into account the strong, extended, and inhomogeneous night sky background (NSB) in the η Car field of view. Tailored run-wise Monte-Carlo simulations (RWS) were required to accurately treat the additional noise from NSB photons in the instrument response functions. Results. H.E.S.S. detected VHE γ-ray emission from the direction of η Car shortly before and after the minimum in the X-ray light-curve close to periastron. Using the point spread function provided by RWS, the reconstructed signal is point-like and the spectrum is best described by a power law. The overall flux and spectral index in VHE γ rays agree within statistical and systematic errors before and after periastron. The γ-ray spectrum extends up to at least 400 GeV. This implies a maximum magnetic field in a leptonic scenario in the emission region of 0.5 Gauss. No indication for phase-locked flux variations is detected in the H.E.S.S. data.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Astroparticle physics; Binaries: general; Cosmic rays; Radiation mechanisms: non-thermal; Stars: individual: η Car; Stars: Wolf-Rayet

Discovery of Gamma Rays from the Quiescent Sun with HAWC - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Belmont-Moreno, E.; Brisbois, C.; Caballero-Mora, K. S.; Capistrán, T.; Carramiñana, A.; et al. (Physical Review Letters, 2023)
We report the first detection of a TeV γ-ray flux from the solar disk (6.3σ), based on 6.1 years of data from the High Altitude Water Cherenkov (HAWC) observatory. The 0.5-2.6 TeV spectrum is well fit by a power law, dN/dE=A(E/1 TeV)-γ, with A=(1.6±0.3)×10-12 TeV-1 cm-2 s-1 and γ=3.62±0.14. The flux shows a strong indication of anticorrelation with solar activity. These results extend the bright, hard GeV emission from the disk observed with Fermi-LAT, seemingly due to hadronic Galactic cosmic rays showering on nuclei in the solar atmosphere. However, current theoretical models are unable to explain the details of how solar magnetic fields shape these interactions. HAWC's TeV detection thus deepens the mysteries of the solar-disk emission.
CRIS-Team Scopus Importer:2023-08-25

Electron spectrum of the dragonfly pulsar wind nebula from X-ray to TeV - Brisbois, Chad; Joshi, Vikas (Proceedings of Science, 2019)
The Dragonfly nebula is a Vela-like Pulsar Wind Nebula (PWN) in the Cygnus region powered by the spin down of PSR J2021+3651. In X-rays, the inner nebula is a few arcseconds across, whereas at TeV energies VERITAS and HAWC has observed extended emission much larger than the extension in X-rays. The TeV gamma-ray source HAWC J2019+368 was originally discovered in 2007 by the Milagro Observatory and has been associated with this pulsar. Recent work has shown hints of energy dependent morphology for the source at TeV energies, supporting the interpretation of the gamma-ray emission being due to Inverse Compton scattering of electrons and positrons from interstellar radiation fields and cosmic microwave background photons. The hard spectral index and spectral softening above 30 TeV of the source are consistent with Klein-Nishina suppression of the electron-photon cross-section at high energies. We will present our most recent studies in modeling and analysis of HAWC J2019+368, explaining the X-ray and TeV emission up to the highest energies using the latest data from the HAWC Observatory.
CRIS-Team Scopus Importer:2021-04-20

Evidence for γ-ray emission from the remnant of Kepleras supernova based on deep H.E.S.S. observations - Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlöhr, K.; Böttcher, M.; Boisson, C.; et al. (Astronomy & Astrophysics, 2022)
Observations with imaging atmospheric Cherenkov telescopes (IACTs) have enhanced our knowledge of nearby supernova (SN) remnants with ages younger than 500 yr by establishing Cassiopeia A and the remnant of Tychoas SN as very-high-energy (VHE) ?-ray sources. The remnant of Kepleras SN, which is the product of the most recent naked-eye SN in our Galaxy, is comparable in age to the other two, but is significantly more distant. If the ?-ray luminosities of the remnants of Tychoas and Kepleras SNe are similar, then the latter is expected to be one of the faintest ?-ray sources within reach of the current generation IACT arrays. Here we report evidence at a statistical level of 4.6? for a VHE signal from the remnant of Kepleras SN based on deep observations by the High Energy Stereoscopic System (H.E.S.S.) with an exposure of 152 h. The measured integral flux above an energy of 226 GeV is ?0.3% of the flux of the Crab Nebula. The spectral energy distribution (SED) reveals a ?-ray emitting component connecting the VHE emission observed with H.E.S.S.To the emission observed at GeV energies with Fermi-LAT. The overall SED is similar to that of the remnant of Tychoas SN, possibly indicating the same nonthermal emission processes acting in both these young remnants of thermonuclear SNe.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Gamma rays: General; Ism: Supernova remnants; Radiation mechanisms: Non-Thermal; Supernovae: Individual: Kepler

Evidence of 200 TeV photons from HAWC J1825-134 - Albert, A.; Alfaro, R.; Alvarez, C.; Camacho, J. R. Angeles; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Ayala Solares, H. A.; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; et al. (Astrophysical Journal Letters, 2021)
The Earth is bombarded by ultrarelativistic particles, known as cosmic rays (CRs). CRs with energies up to a few PeV (=1015 eV), the knee in the particle spectrum, are believed to have a Galactic origin. One or more factories of PeV CRs, or PeVatrons, must thus be active within our Galaxy. The direct detection of PeV protons from their sources is not possible since they are deflected in the Galactic magnetic fields. Hundred TeV γ-rays from decaying π0, produced when PeV CRs collide with the ambient gas, can provide the decisive evidence of proton acceleration up to the knee. Here we report the discovery by the High Altitude Water Cerenkov (HAWC) observatory of the γ-ray source, HAWC J1825-134, whose energy spectrum extends well beyond 200 TeV without a break or cutoff. The source is found to be coincident with a giant molecular cloud. The ambient gas density is as high as 700 protons cm-3. While the nature of this extreme accelerator remains unclear, CRs accelerated to energies of several PeV colliding with the ambient gas likely produce the observed radiation.
CRIS-Team Scopus Importer:2021-02-26

Evidence that Ultra-high-energy Gamma Rays Are a Universal Feature near Powerful Pulsars - Albert, A.; Alfaro, R.; Alvarez, C.; Alvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Ayala Solares, H. A.; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; et al. (Astrophysical Journal Letters, 2021)
The highest-energy known gamma-ray sources are all located within 0.°5 of extremely powerful pulsars. This raises the question of whether ultra-high-energy (UHE; >56 TeV) gamma-ray emission is a universal feature expected near pulsars with a high spin-down power. Using four years of data from the High Altitude Water Cherenkov Gamma-Ray Observatory, we present a joint-likelihood analysis of 10 extremely powerful pulsars to search for subthreshold UHE gamma-ray emission correlated with these locations. We report a significant detection (>3σ), indicating that UHE gamma-ray emission is a generic feature of powerful pulsars. We discuss the emission mechanisms of the gamma rays and the implications of this result. The individual environment, such as the magnetic field and particle density in the surrounding area, appears to play a role in the amount of emission.
CRIS-Team Scopus Importer:2021-05-14

Galactic Cosmic Ray increase associated with an interplanetary magnetic cloud observed by HAWC - Lara, Alejandro; Arunbabu, K. P.; Niembro, Tatiana; Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; et al. (Proceedings of Science, 2022)
We present the observation of an anomalous increment of the galactic cosmic ray (GCR) flux observed by the HAWC array during October 2016. We propose that this anisotropy of the GCR flux was caused by a magnetic flux rope (MFR) i. e., by the helicoidal magnetic field of an interplanetary coronal mass ejection observed at 1 AU at the same time. We computed the trajectory of protons with energy in the range of 10 to 60 GeV, traveling inside the helicoidal magnetic field observed in situ. The direction of these particles changes towards the axis of the MFR resulting in an anisotropy of the GCR flux along this axis. This model shows that the alignment between the MFR axis and the HAWC's asymptotic direction, combined with the high sensitivity of HAWC, allowed us to observe the effect of the passage of the MFR on the GCR flux. We present the HAWC observation associated with the passage of the MFR as well as the heliospheric circumstances around such phenomenon.
CRIS-Team Scopus Importer:2022-12-23

Galactic gamma-ray and neutrino emission from interacting cosmic-ray nuclei - Breuhaus, M.; Hinton, J. A.; Joshi, Vikas; Reville, B.; Schoorlemmer, H. (Astronomy & Astrophysics, 2022)
We present a study of the expectations for very-high-energy (VHE) to ultra-high-energy (UHE) gamma-ray and neutrino emission from interacting cosmic rays in our Galaxy as well as a comparison to the latest results for the Galactic UHE diffuse emission. We demonstrate the importance of properly accounting for both the mixed cosmic-ray composition and the gamma-ray absorption. We adopt the wounded-nucleon model of nucleus interactions and provide parameterisations of the resulting gamma-ray and neutrino production. Nucleon shielding due to clustering inside nuclei is shown to have a measurable effect on the production of gamma rays and is particularly evident close to breaks and cutoffs in mixed-composition particle spectra. The change in composition around the 'knee' in the cosmic ray spectrum has a noticeable impact on the diffuse neutrino and gamma-ray emission spectra. We show that current and near-future detectors can probe these differences in the key energy range from 10 TeV to 1 PeV, testing the paradigm of the universality of the cosmic ray spectrum and composition throughout the Galaxy.
CRIS-Team WoS Importer:2022-05-20
Keywords: radiation mechanisms: non-thermal; cosmic rays; neutrinos; gamma rays: ISM

Galactic Gamma-Ray Diffuse Emission at TeV Energies with HAWC Data - Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Babu, R.; Baghmanyan, V.; Belmont-Moreno, E.; Brisbois, C.; Caballero-Mora, K. S.; Capistrán, T.; Carramiñana, A.; et al. (Astrophysical Journal, 2024)
Galactic gamma-ray diffuse emission (GDE) is emitted by cosmic rays (CRs), ultra-relativistic protons, and electrons, interacting with gas and electromagnetic radiation fields in the interstellar medium. Here we present the analysis of teraelectronvolt diffuse emission from a region of the Galactic plane over the range in longitude of l ∈ [43°, 73°], using data collected with the High Altitude Water Cherenkov (HAWC) detector. Spectral, longitudinal, and latitudinal distributions of the teraelectronvolt diffuse emission are shown. The radiation spectrum is compatible with the spectrum of the emission arising from a CR population with an index similar to that of the observed CRs. When comparing with the DRAGON base model, the HAWC GDE flux is higher by about a factor of 2. Unresolved sources such as pulsar wind nebulae and teraelectronvolt halos could explain the excess emission. Finally, deviations of the Galactic CR flux from the locally measured CR flux may additionally explain the difference between the predicted and measured diffuse fluxes.
CRIS-Team Scopus Importer:2024-02-09

Galactic Gamma-Ray Diffuse Emission at TeV energies with HAWC Data - Grasso, D.; Marinelli, A.; Gaggero, D.; Ventura, S.; Fornieri, O.; Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; et al. (Proceedings of Science, 2022)
The Galactic gamma-ray diffuse emission is produced by the interaction of cosmic rays with ambient gas and electromagnetic radiation fields in the interstellar medium (ISM). Studying this radiation helps reconstruct the particle transport mechanisms and the particle distribution in the Galaxy. In this work, we analyze the TeV diffuse emission in a chosen region of the Galactic plane using data collected with the High Altitude Water Cherenkov (HAWC) detector. The energy and spatial distributions of the diffuse Galactic gamma-ray radiation have been studied after subtracting extended and point sources detected with greater than 5 sigma significance from the region map. The spectral feature of the aforementioned emission is compatible with the gamma-ray emissivity obtained from the locally measured proton and heavier nuclei spectrum, convolved with the gas distribution in the Galaxy.
CRIS-Team Scopus Importer:2024-12-16

Gamma/hadron separation with the HAWC observatory - Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Belmont-Moreno, E.; Brisbois, C.; Caballero-Mora, K. S.; Capistrán, T.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2022)
The High Altitude Water Cherenkov (HAWC) gamma-ray observatory observes atmospheric showers produced by incident gamma rays and cosmic rays with energy from 300 GeV to more than 100 TeV. A crucial phase in analyzing gamma-ray sources using ground-based gamma-ray detectors like HAWC is to identify the showers produced by gamma rays or hadrons. The HAWC observatory records roughly 25,000 events per second, with hadrons representing the vast majority (>99.9%) of these events. The standard gamma/hadron separation technique in HAWC uses a simple rectangular cut involving only two parameters. This work describes the implementation of more sophisticated gamma/hadron separation techniques, via machine learning methods (boosted decision trees and neural networks), and summarizes the resulting improvements in gamma/hadron separation obtained in HAWC.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Crab Nebula; G/H separation; High energy; Machine Learning

Halo fraction in TeV-bright pulsar wind nebulae - Giacinti, G.; Mitchell, Alison M. W.; Lopez-Coto, R.; Joshi, Vikas; Parsons, R. D.; Hinton, J. A. (Astronomy & Astrophysics, 2020)
The discovery of extended TeV emission around the Geminga and PSR B0656+14 pulsars, with properties consistent with free particle propagation in the interstellar medium (ISM), has led to the suggestion of "TeV halos" as a separate source class, which is distinct from pulsar wind nebulae. This has sparked considerable discussion on the possible presence of such halos in other systems. In defining halos as regions where the pulsar no longer dominates the dynamics of the interstellar medium, yet where an over-density of relativistic electrons is present, we make an assessment of the current TeV source population associated with energetic pulsars in terms of size and estimated energy density. Based on two alternative estimators, we conclude that a large majority of the known TeV sources have emission originating in the zone that is energetically and dynamically dominated by the pulsar (i.e. the pulsar wind nebula), rather than from a surrounding halo of escaped particles diffusing into the ISM. Furthermore, whilst the number of established halos will surely increase in the future since there is a known large population of older, less energetic pulsars, we find that it is unlikely that such halos contribute significantly to the total TeV gamma -ray luminosity from electrons accelerated in pulsar wind nebulae due to their lower intrinsic surface brightness.
CRIS-Team WoS Importer:2020-05-19
Keywords: Pulsars: general; Diffusion; Gamma rays: general; Cosmic rays

HAWC and Fermi-LAT Detection of Extended Emission from the Unidentified Source 2HWC J2006+341 - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Araya, M.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Baghmanyan, V.; Belmont-Moreno, E.; Brisbois, C.; et al. (Astrophysical Journal Letters, 2020)
The discovery of the TeV point source 2HWC J2006+341 was reported in the second HAWC gamma-ray catalog. We present a follow-up study of this source here. The TeV emission is best described by an extended source with a soft spectrum. At GeV energies, an extended source is significantly detected in Fermi-LAT data. The matching locations, sizes, and spectra suggest that both gamma-ray detections correspond to the same source. Different scenarios for the origin of the emission are considered and we rule out an association to the pulsar PSR J2004 +3429 due to extreme energetics required, if located at a distance of 10.8 kpc.
CRIS-Team Scopus Importer:2020-11-20

HAWC as a Ground-Based Space-Weather Observatory - Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Baghmanyan, V.; Belmont-Moreno, E.; BenZvi, S. Y.; Brisbois, C.; Caballero-Mora, K. S.; Capistrán, T.; Colín-Farias, P.; et al. (Solar Physics, 2021)
The High Altitude Water Cherenkov (HAWC) gamma-ray observatory is located close to the equator (latitude 18 ∘ N), at an altitude of 4100 m above sea level. HAWC has 295 water Cherenkov detectors (WCD), each containing four photomultiplier tubes (PMT). The main purpose of HAWC is the determination of the energy and arrival direction of very high energy gamma rays produced by energetic processes in the universe, HAWC also has a scaler system which counts the arrival of secondary particles to the detector. In this work we show that the scaler system of HAWC is an ideal instrument for solar modulation and space-weather studies due to its large area and high sensitivity. In order to prepare the scaler system for low energy heliospheric studies, we model and correct the efficiency variation of each PMT of the array, which result in a capability to measure variations > 0.01 % with high accuracy. Using the singular value decomposition method, we correct the rate deviations of all PMTs of the array, due to changes in efficiency, gain and operational voltage. We isolate and remove the atmospheric modulations of the PMTs count rates measured by the TDC-scaler data acquisition system. In particular, the atmospheric pressure at the HAWC site exhibits an oscillating behavior with a period of ∼12 hours and we make use of this periodic property to estimate the pressure coefficients for the HAWC TDC-scaler system. These corrections performed on the TDC-scaler system make the HAWC TDC-scaler system an ideal instrument for solar modulation and space-weather studies. As examples of this capability, we present the preliminary analysis of the solar modulation of cosmic rays at three time scales observed by HAWC, with an unprecedented accuracy.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Atmospheric pressure modulation; Cosmic rays; Fast Fourier transform; Solar modulation

HAWC Detection of a TeV Halo Candidate Surrounding a Radio-quiet Pulsar - Albert, A.; Alfaro, R.; Arteaga-Velázquez, J. C.; Ayala Solares, H. A.; Belmont-Moreno, E.; Capistrán, T.; Carramiñana, A.; Casanova, S.; Cotzomi, J.; De León, S. Coutiño; Fuente, E. De la; de León, C.; et al. (Astrophysical Journal Letters, 2023)
Extended very-high-energy (VHE; 0.1-100 TeV) γ-ray emission has been observed around several middle-aged pulsars and referred to as “TeV halos.” Their formation mechanism remains under debate. It is also unknown whether they are ubiquitous or related to a certain subgroup of pulsars. With 2321 days of observation, the High Altitude Water Cherenkov (HAWC) Gamma-Ray Observatory detected VHE γ-ray emission at the location of the radio-quiet pulsar PSR J0359+5414 with >6σ significance. By performing likelihood tests with different spectral and spatial models and comparing the TeV spectrum with multiwavelength observations of nearby sources, we show that this excess is consistent with a TeV halo associated with PSR J0359+5414, though future observation of HAWC and multiwavelength follow-ups are needed to confirm this nature. This new halo candidate is located in a noncrowded region in the outer galaxy. It shares similar properties to the other halos but its pulsar is younger and radio-quiet. Our observation implies that TeV halos could commonly exist around pulsars and their formation does not depend on the configuration of the pulsar magnetosphere.
CRIS-Team Scopus Importer:2023-03-03

HAWC J2227+610 and Its Association with G106.3+2.7, a New Potential Galactic PeVatron - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; et al. (Astrophysical Journal Letters, 2020)
We present the detection of very-high-energy gamma-ray emission above 100 TeV from HAWC J2227+610 with the High-Altitude Water Cherenov Gamma-Ray Observatory (HAWC) observatory. Combining our observations with previously published results by the Very Energetic Radiation Imaging Telescope Array System (VERTIAS), we interpret the gamma-ray emission from HAWC J2227+610 as emission from protons with a lower limit in their cutoff energy of 800 TeV. The most likely source of the protons is the associated supernova remnant G106.3+2.7, making it a good candidate for a Galactic PeVatron. However, a purely leptonic origin of the observed emission cannot be excluded at this time.
CRIS-Team Scopus Importer:2020-07-10

HAWC observations of the acceleration of very-high-energy cosmic rays in the Cygnus Cocoon - Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Camacho, J. R.Angeles; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Solares, H. A.Ayala; Baghmanyan, V.; Belmont-Moreno, E.; BenZvi, S. Y.; et al. (Nature Astronomy, 2021)
Cosmic rays with energies up to a few PeV are known to be accelerated within the Milky Way1,2. Traditionally, it has been presumed that supernova remnants were the main source of these very-high-energy cosmic rays3,4, but theoretically it is difficult to accelerate protons to PeV energies5,6 and observationally there simply is no evidence of the remnants being sources of hadrons with energies above a few tens of TeV7,8. One possible source of protons with those energies is the Galactic Centre region9. Here, we report observations of 1–100 TeV γ rays coming from the ‘Cygnus Cocoon’10, which is a superbubble that surrounds a region of massive star formation. These γ rays are likely produced by 10–1,000 TeV freshly accelerated cosmic rays that originate from the enclosed star-forming region Cyg OB2. Until now it was not known that such regions could accelerate particles to these energies. The measured flux likely originates from hadronic interactions. The spectral shape and the emission profile of the Cocoon changes from GeV to TeV energies, which reveals the transport of cosmic particles and historical activity in the superbubble.
CRIS-Team Scopus Importer:2021-04-02

HAWC Search for High-mass Microquasars - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; et al. (Astrophysical Journal Letters, 2021)
Microquasars with high-mass companion stars are promising very high energy (VHE; 0.1-100 TeV) gamma-ray emitters, but their behaviors above 10 TeV are poorly known. Using the High Altitude Water Cerenkov (HAWC) observatory, we search for excess gamma-ray emission coincident with the positions of known high-mass microquasars (HMMQs). No significant emission is observed for LS 5039, Cyg X-1, Cyg X-3, and SS 433 with 1523 days of HAWC data. We set the most stringent limit above 10 TeV obtained to date on each individual source. Under the assumption that HMMQs produce gamma rays via a common mechanism, we have performed source-stacking searches, considering two different scenarios: (I) gamma-ray luminosity is a fraction epsilon ( gamma ) of the microquasar jet luminosity, and (II) VHE gamma rays are produced by relativistic electrons upscattering the radiation field of the companion star in a magnetic field B. We obtain epsilon ( gamma ) < 5.4 x 10(-6) for scenario I, which tightly constrains models that suggest observable high-energy neutrino emission by HMMQs. In the case of scenario II, the nondetection of VHE gamma rays yields a strong magnetic field, which challenges synchrotron radiation as the dominant mechanism of the microquasar emission between 10 keV and 10 MeV.
CRIS-Team WoS Importer:2021-05-21

HAWC Study of the Ultra-high-energy Spectrum of MGRO J1908+06 - Albert, A.; Alfaro, R.; Alvarez, C.; Alvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Avila Rojas, D.; Solares, H. A. Ayala; Babu, R.; Belmont-Moreno, E.; Brisbois, C.; Caballero-Mora, K. S.; et al. (Astrophysical Journal, 2022)
We report TeV gamma-ray observations of the ultra-high-energy source MGRO J1908+06 using data from the High Altitude Water Cherenkov Observatory. This source is one of the highest-energy known gamma-ray sources, with emission extending past 200 TeV. Modeling suggests that the bulk of the TeV gamma-ray emission is leptonic in nature, driven by the energetic radio-faint pulsar PSR J1907+0602. Depending on what assumptions are included in the model, a hadronic component may also be allowed. Using the results of the modeling, we discuss implications for detection prospects by multi-messenger campaigns.
CRIS-Team WoS Importer:2022-04-22
Keywords: Gamma-ray sources; Gamma-rays; Pulsars; Supernova remnants; Gamma-ray astronomy

HAWC Study of the Very-high-energy γ-Ray Spectrum of HAWC J1844−034 - Albert, A.; Alvarez, C.; Rojas, D. Avila; Solares, H. A.Ayala; Babu, R.; Belmont-Moreno, E.; Breuhaus, M.; Capistrán, T.; Carramiñana, A.; Casanova, S.; Cotzomi, J.; de León, S. Coutiño; et al. (Astrophysical Journal, 2023)
Recently, the region surrounding eHWC J1842−035 has been studied extensively by γ-ray observatories due to its extended emission reaching up to a few hundred TeV and potential as a hadronic accelerator. In this work, we use 1910 days of cumulative data from the High Altitude Water Cherenkov (HAWC) observatory to carry out a dedicated systematic source search of the eHWC J1842−035 region. During the search, we found three sources in the region, namely, HAWC J1844−034, HAWC J1843−032, and HAWC J1846−025. We have identified HAWC J1844−034 as the extended source that emits photons with energies up to 175 TeV. We compute the spectrum for HAWC J1844−034, and by comparing with the observational results from other experiments, we have identified HESS J1843−033, LHAASO J1843−0338, and TASG J1844−038 as very-high-energy γ-ray sources with a matching origin. Also, we present and use the multiwavelength data to fit the hadronic and leptonic particle spectra. We have identified four pulsar candidates in the nearby region in which PSR J1844−0346 is found to be the most likely candidate due to its proximity to HAWC J1844−034 and the computed energy budget. We have also found SNR G28.6−0.1 as a potential counterpart source of HAWC J1844−034 for which both leptonic and hadronic scenarios are feasible.
CRIS-Team Scopus Importer:2023-09-22

HESS J1809-193: A halo of escaped electrons around a pulsar wind nebula? - Aharonian, F.; Ait Benkhali, F.; Aschersleben, J.; Ashkar, H.; Backes, M.; Barbosa Martins, V.; Batzofin, R.; Becherini, Y.; Berge, D.; Boettcher, M.; Boisson, C.; Bolmont, J.; et al. (Astronomy & Astrophysics, 2023)
Context. HESS J1809-193 is an unassociated very-high-energy gamma-ray source located on the Galactic plane. While it has been connected to the nebula of the energetic pulsar PSR J1809-1917, supernova remnants and molecular clouds present in the vicinity also constitute possible associations. Recently, the detection of gamma-ray emission up to energies of similar to 100 TeV with the HAWC observatory has led to renewed interest in HESS J1809-193.Aims. We aim to understand the origin of the gamma-ray emission of HESS J1809-193.Methods. We analysed 93.2 h of data taken on HESS J1809-193 above 0.27 TeV with the High Energy Stereoscopic System (H.E.S.S.), using a multi-component, three-dimensional likelihood analysis. In addition, we provide a new analysis of 12.5 yr of Fermi-LAT data above 1 GeV within the region of HESS J1809-193. The obtained results are interpreted in a time-dependent modelling framework.Results. For the first time, we were able to resolve the emission detected with H.E.S.S. into two components: an extended component (modelled as an elongated Gaussian with a 1-sigma semi-major and semi-minor axis of similar to 0.62 degrees and similar to 0.35 degrees, respectively) that exhibits a spectral cutoff at similar to 13 TeV, and a compact component (modelled as a symmetric Gaussian with a 1-sigma radius of similar to 0.1 degrees) that is located close to PSR J1809-1917 and shows no clear spectral cutoff. The Fermi-LAT analysis also revealed extended gamma-ray emission, on scales similar to that of the extended H.E.S.S. component.Conclusions. Our modelling indicates that based on its spectrum and spatial extent, the extended H.E.S.S. component is likely caused by inverse Compton emission from old electrons that form a halo around the pulsar wind nebula. The compact component could be connected to either the pulsar wind nebula or the supernova remnant and molecular clouds. Due to its comparatively steep spectrum, modelling the Fermi-LAT emission together with the H.E.S.S. components is not straightforward.
CRIS-Team WoS Importer:2023-05-05

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Alfaro, Ruben; Alvarez, César; Arteaga-Velázquez, Juan Carlos; Kollamparambil Paul, Arun Babu; Rojas, Daniel Avila; Ayala Solares, Hugo Alberto; Babu, Rishi; Belmont-Moreno, Ernesto; Brisbois, Chad; Caballero-Mora, Karen S.; Capistrán, Tomás; Carramiñana, Alberto; et al. (Advances in Space Research, 2023)
High-energy cosmic rays that hit the Earth can be used to study large-scale atmospheric perturbations. After a first interaction in the upper parts of the atmosphere, cosmic rays produce a shower of particles that sample it down to the detector level. The HAWC (High-Altitude Water Cherenkov) gamma-ray observatory in Central Mexico at 4,100 m elevation detects air shower particles continuously with 300 water Cherenkov detectors with an active area of 12,500 m2. On January 15th, 2022, HAWC detected the passage of the pressure wave created by the explosion of the Hunga volcano in the Tonga islands, 9,000 km away, as an anomaly in the measured rate of shower particles. The HAWC measurements are used to determine the propagation speed of four pressure wave passages, and correlate the variations of the shower particle rates with the barometric pressure changes. The profile of the shower particle rate and atmospheric pressure variations for the first transit of the pressure wave at HAWC is compared to the pressure measurements at the Tonga island, near the volcanic explosion. By using the cosmic-ray propagation in the atmosphere as a probe for the pressure, it is possible to achieve very high time-resolution measurements. Moreover, the high-altitude data from HAWC allows to observe the shape of the pressure anomaly with less perturbations compared to sea level detectors. Given the particular location and the detection method of HAWC, our high-altitude data provides valuable information that contributes to fully characterize this once-in-a-century phenomenon.
CRIS-Team Scopus Importer:2023-10-27
Keywords: Cosmic rays; HAWC observatory; Hunga volcano; Lamb wave

Interplanetary Magnetic Flux Rope Observed at Ground Level by HAWC - Akiyama, S.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Solares, H. A. Ayala; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistran, T.; Carraminana, A.; et al. (Astrophysical Journal, 2020)
We report the ground-level detection of a Galactic cosmic-ray (GCR) flux enhancement lasting similar to 17 hr and associated with the passage of a magnetic flux rope (MFR) over the Earth. The MFR was associated with a slow coronal mass ejection (CME) caused by the eruption of a filament on 2016 October 9. Due to the quiet conditions during the eruption and the lack of interactions during the interplanetary CME transport to the Earth, the associated MFR preserved its configuration and reached the Earth with a strong magnetic field, low density, and a very low turbulence level compared to local background, thus generating the ideal conditions to redirect and guide GCRs (in the similar to 8-60 GV rigidity range) along the magnetic field of the MFR. An important negative B-Z component inside the MFR caused large disturbances in the geomagnetic field and a relatively strong geomagnetic storm. However, these disturbances are not the main factors behind the GCR enhancement. Instead, we found that the major factor was the alignment between the MFR axis and the asymptotic direction of the observer.
CRIS-Team WoS Importer:2021-01-01

Limits on Diffuse Dark Matter with HAWC - Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Baghmanyan, V.; et al. (Proceedings of Science, 2022)
In addition to dense regions of dark matter, such as galaxy clusters and dwarf galaxies, dark matter annihilation and decay are also expected to have a nearly isotropic distribution across the sky. This isotropic component is less model-dependent than the flux from isolated dark matter targets, and would produce galactic contributions to the Diffuse Gamma-Ray Background (DGRB). With its continuous monitoring of the gamma-ray sky from a few hundred GeV to several hundred TeV and its wide field-of-view, the High Altitude Water Cherenkov (HAWC) observatory is well-suited to search for dark matter contributions in the DGRB. In this work, 535 days of HAWC data and Monte Carlo simulations were studied to set limits on annihilating or decaying diffuse dark matter at TeV energies. With this data, we consider both leptonic and hadronic dark matter channels and are able to constrain dark matter up to masses >100 TeV.
CRIS-Team Scopus Importer:2024-12-16

Limits on the Diffuse Gamma-Ray Background with HAWC - Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Baghmanyan, V.; et al. (Proceedings of Science, 2022)
The high-energy Diffuse Gamma-Ray Background (DGRB) is expected to be produced by unresolved extra-galactic objects such as active galactic nuclei, starburst galaxies and gamma-ray bursts. At TeV energies, observations or stringent limits on the DGRB could have significant multi-messenger implications, such as constraining the origin of TeV-PeV astrophysical neutrinos detected by IceCube. With its continuous sensitivity to gamma rays from a few hundred GeV to several hundred TeV and its wide field-of-view, the High Altitude Water Cherenkov (HAWC) observatory is well-suited to significantly improve searches for the DGRB. In this work, strict cuts have been applied to the HAWC dataset to better isolate gamma-ray air showers from background hadronic showers. The sensitivity to the DGRB was then verified using 535 days of Crab data and Monte Carlo simulations, leading to new limits on the DGRB >10 TeV.
CRIS-Team Scopus Importer:2024-12-16

Long-term Spectra of the Blazars Mrk 421 and Mrk 501 at TeV Energies Seen by HAWC - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Baghmanyan,; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistran, T.; et al. (Astrophysical Journal, 2022)
The High Altitude Water Cherenkov (HAWC) Gamma-Ray Observatory surveys the very high-energy sky in the 300 GeV to >100 TeV energy range. HAWC has detected two blazars above 11 sigma, Markarian 421 (Mrk 421) and Markarian 501 (Mrk 501). The observations are comprised of data taken in the period between 2015 June and 2018 July, resulting in similar to 1038 days of exposure. In this work, we report the time-averaged spectral analyses for both sources, above 0.5 TeV. Taking into account the flux attenuation due to the extragalactic background light, the intrinsic spectrum of Mrk 421 is described by a power law with an exponential energy cutoff with index alpha = 2.26 +/- (0.12)(stat)((+0.17)(-0.2))(sys) and energy cutoff E-c = 5.1 +/- (1.6)(stat)((+1.4)(-2.5))(sys) TeV, while the intrinsic spectrum of Mrk 501 is better described by a simple power law with index alpha = 2.61 +/- (0.11)(stat)((+)(0.01)(-0.07))(sys). The maximum energies at which the Mrk 421 and Mrk 501 signals are detected are 9 and 12 TeV, respectively. This makes these some of the highest energy detections to date for spectra averaged over years-long timescales. Since the observation of gamma radiation from blazars provides information about the physical processes that take place in their relativistic jets, it is important to study the broadband spectral energy distributions (SEDs) of these objects. For this purpose, contemporaneous data in the gamma-ray band to the X-ray range, and literature data in the radio to UV range, were used to build time-averaged SEDs that were modeled within a synchrotron-self Compton leptonic scenario.
CRIS-Team WoS Importer:2022-05-13

Modeling the non-flaring VHE emission from M87 as detected by the HAWC gamma ray observatory - Ureña-Mena, Fernando; Carramiñana, Alberto; Longinotti, Anna Lia; Rosa-González, Daniel; Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; et al. (Proceedings of Science, 2022)
M87 is a giant radio galaxy located in the Virgo Cluster, known to be a very high energy (VHE) gamma-ray source. As radio galaxies are considered the misaligned low-redshift counterparts of blazars, they are excellent laboratories for testing AGN emission models. M87 has been detected and monitored by Fermi-LAT and several atmospheric Cherenkov telescopes. Recently, the HAWC Collaboration presented marginal evidence of 4.5 year TeV gamma-ray emission from this object. The HAWC data has the potential to constrain the average VHE emission of sources of complex behavior, like M87, for which the physical origin of the VHE gamma-ray emission is still uncertain. We fitted a lepto-hadronic scenario to the broadband spectral energy distribution of M87 to model its non-flaring VHE emission using HAWC data.
CRIS-Team Scopus Importer:2024-12-16

Multimessenger gamma-ray and neutrino coincidence alerts using hawc and icecube subthreshold data - Solares, H. A.Ayala; Coutu, S.; DeLaunay, J. J.; Fox, D. B.; Grégoire, T.; Keivani, A.; Krauß, F.; Mostafá, M.; Murase, K.; Turley, C. F.; Albert, A.; Alfaro, R.; et al. (Astrophysical Journal, 2021)
The High Altitude Water Cerenkov (HAWC) and IceCube observatories, through the Astrophysical Multimessenger Observatory Network (AMON) framework, have developed a multimessenger joint search for extragalactic astrophysical sources. This analysis looks for sources that emit both cosmic neutrinos and gamma rays that are produced in photohadronic or hadronic interactions. The AMON system is running continuously, receiving subthreshold data (i.e., data that are not suited on their own to do astrophysical searches) from HAWC and IceCube, and combining them in real time. Here we present the analysis algorithm, as well as results from archival data collected between 2015 June and 2018 August, with a total live time of 3.0 yr. During this period we found two coincident events that have a false-alarm rate (FAR) of <1 coincidence yr-1, consistent with the background expectations. The real-time implementation of the analysis in the AMON system began on 2019 November 20 and issues alerts to the community through the Gamma-ray Coordinates Network with an FAR threshold of <4 coincidences yr-1.
CRIS-Team Scopus Importer:2021-01-22

Multiple Galactic Sources with Emission Above 56 TeV Detected by HAWC - Albert, A.; Alfaro, R.; Avila Rojas, D.; Baghmanyan, V.; Belmont-Moreno, E.; Brisbois, C.; Capistran, T.; Carraminana, A.; Casanova, S.; Cotti, U.; Cotzomi, J.; Coutino De Leon, S.; et al. (Physical Review Letters, 2020)
We present the first catalog of gamma-ray sources emitting above 56 and 100 TeV with data from the High Altitude Water Cherenkov Observatory, a wide field-of-view observatory capable of detecting gamma rays up to a few hundred TeV. Nine sources are observed above 56 TeV, all of which are likely galactic in origin. Three sources continue emitting past 100 TeV, making this the highest-energy gamma-ray source catalog to date. We report the integral flux of each of these objects. We also report spectra for three high-estenergy sources and discuss the possibility that they are PeVatrons.
CRIS-Team WoS Importer:2020-01-31

Particle Acceleration in the Cygnus Superbubble - Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Baghmanyan, V.; et al. (Proceedings of Science, 2022)
The Cygnus Cocoon is the first gamma-ray superbubble powered by a massive stellar association, the OB2 association. It was postulated that the combined effects of the stellar winds of all the massive O-type stars of the OB2 association can accelerate the cosmic rays to PeV energy in the Cocoon. The conclusive proof of acceleration to PeV energy in the Cocoon will identify the stellar association as a PeV cosmic-ray accelerator, known as PeVatron. However, the Cocoon has been previously studied only up to 10 TeV. In this contribution, using 1343 days of High Altitude Water Cherenkov (HAWC) observatory data, we present the morphological and spectral study of the Cocoon above 1 TeV to beyond 100 TeV. The analysis at higher TeV energies reveals a softer spectrum compared to the GeV gamma-ray observation. This result suggests that the accelerator's efficiency decreases around hundreds of TeV, or after being accelerated, the highest-energy protons escape the region. The study above 10 TeV presented here demonstrates how CR accelerators operate in these extreme energies and how particle transport impacts high-energy emission.
CRIS-Team Scopus Importer:2024-12-16

Precise Measurements of TeV Halos around Geminga and Monogem Pulsars with HAWC - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Belmont-Moreno, E.; Bernal, A.; Caballero-Mora, K. S.; Capistrán, T.; Carramiñana, A.; et al. (Astrophysical Journal, 2024)
We present the most precise measurements to date for the spatial extension and energy spectrum of the γ-ray region between a pulsar’s wind nebula and the interstellar medium, better known as the halo, present around Geminga and PSR B0656+14 (Monogem) using ∼2398 days of >1 TeV data collected by the HAWC observatory. We interpret the data using a physically motivated model for the diffuse γ-ray emission generated from positrons and electrons (e±) injected by the pulsar wind nebula and inverse Compton scattering with interstellar radiation fields. We find the morphologies of the regions inside these halos are characterized by an inhibited diffusion that are approximately three orders of magnitudes smaller than the Galactic average. We also obtain the e± emission efficiencies of 6.6% and 5.1%, respectively, for Geminga and Monogem. These results have remarkable consequences for the study of the particle diffusion in the region between the pulsar wind nebulae and the interstellar medium, and for the interpretation of the flux of positrons measured by the AMS-02 experiment above 10 GeV.
CRIS-Team Scopus Importer:2025-02-04

Probing the Extragalactic Mid-infrared Background with HAWC - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velazquez, J. C.; Rojas, D. Avila; Solares, H. A. Ayala; Babu, R.; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistran, T.; Carraminana, A.; Casanova, S.; et al. (Astrophysical Journal, 2022)
The extragalactic background light (EBL) contains all the radiation emitted by nuclear and accretion processes in stars and compact objects since the epoch of recombination. Measuring the EBL density directly is challenging, especially in the near-to-far-infrared wave band, mainly due to the zodiacal light foreground. Instead, gamma-ray astronomy offers the possibility to indirectly set limits on the EBL by studying the effects of gamma-ray absorption in the very high energy (VHE: >100 GeV) spectra of distant blazars. The High Altitude Water Cherenkov Gamma Ray Observatory (HAWC) is one of the few instruments sensitive to gamma rays with energies above 10 TeV. This offers the opportunity to probe the EBL in the near/mid-IR region: lambda = 1-100 mu m. In this study, we fit physically motivated emission models to Fermi-LAT gigaelectronvolt data to extrapolate the intrinsic teraelectronvolt spectra of blazars. We then simulate a large number of absorbed spectra for different randomly generated EBL model shapes and calculate Bayesian credible bands in the EBL intensity space by comparing and testing the agreement between the absorbed spectra and HAWC extragalactic observations of two blazars. The resulting bands are in agreement with current EBL lower and upper limits, showing a downward trend toward higher wavelength values lambda > 10 mu m also observed in previous measurements.
CRIS-Team WoS Importer:2022-07-29

Probing the Sea of Cosmic Rays by Measuring Gamma-Ray Emission from Passive Giant Molecular Clouds with HAWC - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; et al. (Astrophysical Journal, 2021)
The study of high-energy gamma rays from passive giant molecular clouds (GMCs) in our Galaxy is an indirect way to characterize and probe the paradigm of the "sea" of cosmic rays in distant parts of the Galaxy. By using data from the High Altitude Water Cerenkov (HAWC) Observatory, we measure the gamma-ray flux above 1 TeV of a set of these clouds to test the paradigm. We selected high galactic latitude clouds that are in HAWC's field of view and that are within 1 kpc distance from the Sun. We find no significant excess emission in the cloud regions, nor when we perform a stacked log-likelihood analysis of GMCs. Using a Bayesian approach, we calculate 95% credible interval upper limits of the gamma-ray flux and estimate limits on the cosmic-ray energy density of these regions. These are the first limits to constrain gamma-ray emission in the multi-TeV energy range (>1 TeV) using passive high galactic latitude GMCs. Assuming that the main gamma-ray production mechanism is due to proton-proton interaction, the upper limits are consistent with a cosmic-ray flux and energy density similar to that measured at Earth.
CRIS-Team WoS Importer:2021-07-02

Recent results from the High Altitude Water Cherenkov Observatory - Mostafá, Miguel; Albert, A.; Alfaro, R.; Alvarez, C.; Andrés, A.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistrán, T.; et al. (Proceedings of Science, 2024)
High energy γ-ray observations are an essential probe of cosmic-ray acceleration mechanisms. The detection of the highest energy γ rays and the shortest timescales of variability are the key to improve our understanding of the acceleration processes and the environment of the cosmic accelerators. The High Altitude Water Cherenkov (HAWC) experiment is a large field-of-view, multi-TeV, γ-ray observatory continuously operating at 4100 m a.s.l. since March, 2015. The HAWC observatory has an order of magnitude better sensitivity, angular resolution, and background rejection than the previous generation of water-Cherenkov arrays. The improved performance allows us to discover new TeV sources, to detect transient events, to study the Galactic diffuse emission at TeV energies, to measure or constrain the TeV spectra of GeV γ-ray sources, to search for Galactic Pevatrons, and to improve the upper limits on indirect searches for dark matter and the constrains on Lorentz invariance violation. In this contribution I summarize the most recent results from the HAWC observatory using the latest reconstruction algorithm (Pass 5 production) and I discuss their implications for cosmic-ray acceleration and propagation.
CRIS-Team Scopus Importer:2025-02-04

Revealing x-ray and gamma ray temporal and spectral similarities in the GRB 190829A afterglow - Taylor, Andrew M.; Aharonian, Felix; Romoli, Carlo; Khangulyan, Dmitry; Ruiz-Velasco, Edna; Schüssler, Fabian; Zhu, Sylvia J.; Büchele, Matthias; Eichhorn, Florian; Funk, Stefan; Glawion, Dorit; Jankowsky, David; et al. (Science, 2021)
Gamma-ray bursts (GRBs), which are bright flashes of gamma rays from extragalactic sources followed by fading afterglow emission, are associated with stellar core collapse events. We report the detection of very-high-energy (VHE) gamma rays from the afterglow of GRB 190829A, between 4 and 56 hours after the trigger, using the High Energy Stereoscopic System (H.E.S.S.). The low luminosity and redshift of GRB 190829A reduce both internal and external absorption, allowing determination of its intrinsic energy spectrum. Between energies of 0.18 and 3.3 tera-electron volts, this spectrum is described by a power law with photon index of 2.07 ± 0.09, similar to the x-ray spectrum. The x-ray and VHE gamma-ray light curves also show similar decay profiles. These similar characteristics in the x-ray and gamma-ray bands challenge GRB afterglow emission scenarios.
CRIS-Team Scopus Importer:2021-06-18

Revisiting HESS J1809−193 — a very-high-energy gamma-ray source in a fascinating environment - Mohrmann, L.; Joshi, Vikas; Hinton, J.; Funk, Stefan (Proceedings of Science, 2024)
HESS J1809−193 is one of the unidentified very-high-energy gamma-ray sources in the H.E.S.S. Galactic Plane Survey (HGPS). It is located in a rich environment, with an energetic pulsar and associated X-ray pulsar wind nebula, several supernova remnants, and molecular clouds in the vicinity. Furthermore, HESS J1809−193 was recently detected at energies above 56 TeV with HAWC, which makes it a PeVatron candidate, that is, a source capable of accelerating cosmic rays up to PeV energies. We present a new analysis of the TeV gamma-ray emission of HESS J1809−193 with H.E.S.S., based on improved analysis techniques. We find that the emission is best described by two components with distinct morphologies and energy spectra. We complement this study with an analysis of Fermi-LAT data in the same region. Finally, taking into account further multiwavelength data, we interpret our results both in a hadronic and leptonic framework.
CRIS-Team Scopus Importer:2025-02-04

Search for Dark Matter Annihilation Signals from Unidentified Fermi-LAT Objects with HESS - Abdalla, H.; Spencer, Samuel; Aharonian, Felix; Ait Benkhali, F.; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Barbosa-Martins, V.; et al. (Astrophysical Journal, 2021)
Cosmological N-body simulations show that Milky Way-sized galaxies harbor a population of unmerged dark matter (DM) subhalos. These subhalos could shine in gamma-rays and eventually be detected in gamma-ray surveys as unidentified sources. We performed a thorough selection among unidentified Fermi-Large Area Telescope Objects (UFOs) to identify them as possible tera-electron-volt-scale DM subhalo candidates. We search for very-high-energy (E greater than or similar to 100 GeV) gamma-ray emissions using H.E.S.S. observations toward four selected UFOs. Since no significant very-high-energy gamma-ray emission is detected in any data set of the four observed UFOs or in the combined UFO data set, strong constraints are derived on the product of the velocity-weighted annihilation cross section sigma v by the J factor for the DM models. The 95% confidence level observed upper limits derived from combined H.E.S.S. observations reach sigma vJ values of 3.7 x 10(-5) and 8.1 x 10(-6) GeV(2 )cm(-2 )s(-1) in the W (+) W (-) and tau (+) tau (-) channels, respectively, for a 1 TeV DM mass. Focusing on thermal weakly interacting massive particles, the H.E.S.S. constraints restrict the J factors to lie in the range 6.1 x 10(19)-2.0 x 10(21) GeV(2 )cm(-5) and the masses to lie between 0.2 and 6 TeV in the W (+) W (-) channel. For the tau (+) tau (-) channel, the J factors lie in the range 7.0 x 10(19)-7.1 x 10(20) GeV(2 )cm(-5) and the masses lie between 0.2 and 0.5 TeV. Assuming model-dependent predictions from cosmological N-body simulations on the J-factor distribution for Milky Way-sized galaxies, the DM models with masses >0.3 TeV for the UFO emissions can be ruled out at high confidence level.
CRIS-Team WoS Importer:2021-09-10

Search for decaying dark matter in the Virgo cluster of galaxies with HAWC - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Ayala Solares, H. A.; Babu, R.; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistrán, T.; Carramiñana, A.; Casanova, S.; Cotzomi, J.; et al. (Physical Review D, 2024)
The decay or annihilation of dark matter particles may produce a steady flux of very-high-energy gamma rays detectable above the diffuse background. Nearby clusters of galaxies provide excellent targets to search for the signatures of particle dark matter interactions. In particular, the Virgo cluster spans several degrees across the sky and can be efficiently probed with a wide field-of-view instrument. The High Altitude Water Cherenkov (HAWC) observatory, due to its wide field of view and sensitivity to gamma rays at an energy scale of 300 GeV-100 TeV is well-suited for this search. Using 2141 days of data, we search for γ-ray emission from the Virgo cluster, assuming well-motivated dark matter substructure models. Our results provide some of the strongest constraints on the decay lifetime of dark matter for masses above 10 TeV.
CRIS-Team Scopus Importer:2024-03-29

Search for gamma-ray spectral lines from dark matter annihilation in dwarf galaxies with the High-Altitude Water Cherenkov observatory - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Solares, H. A. Ayala; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; Caballero-Mora, K. S.; Capistran, T.; et al. (Physical Review D, 2020)
Local dwarf spheroidal galaxies (dSphs) are nearby dark-matter dominated systems, making them excellent targets for searching for gamma rays from particle dark matter interactions. If dark matter annihilates or decays directly into two gamma rays (or a gamma ray and a neutral particle), a monochromatic spectral line is created. At TeV energies, no other process is predicted to produce spectral lines, making this a very clean indirect dark matter search channel. With the development of event-by event energy reconstruction, we can now search for spectral lines with the High Altitude Water Cherenkov (HAWC) Observatory. HAWC is a wide field of view survey instrument located in central Mexico that observes gamma rays from similar to 200 GeV to similar to 200 TeV. In this work we present results from a recent search for spectral lines from local, dark matter dominated, dwarf galaxies using 1038 days of HAWC data. We also present updated limits on several continuum channels that were reported in a previous publication. Our gamma-ray spectral line limits are the most constraining obtained so far from 20 TeV to 100 TeV.
CRIS-Team WoS Importer:2020-05-15

Search for TeV decaying dark matter from the Virgo cluster of galaxies - Un Nisa, Mehr; Harding, Pat; Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; et al. (Proceedings of Science, 2022)
Galaxy clusters’ dynamics constitute a major piece of evidence for the existence of dark matter in astrophysical structures. The decay or annihilation of dark matter particles is hypothesized to produce a steady flux of very-high-energy gamma rays correlated with the direction of a cluster of galaxies. The Virgo cluster, being only 16 Mpc away and spanning several degrees across the sky is an excellent target to search for signatures of particle dark matter interactions. The High Altitude Water Cherenkov (HAWC) observatory, due to its wide field of view and sensitivity to gamma rays at an energy-scale of 300 GeV—100 TeV is well-suited to perform the aforementioned search. We perform a search from the Virgo cluster for gamma-ray emission, assuming various dark matter sub-structure models using 1523 days of HAWC data. Our results provide the strongest constraints on the decay life-time of dark matter for masses above 20 TeV.
CRIS-Team Scopus Importer:2024-12-16

Searching for >177 TeV Gamma Rays in the Vicinity of Mrk 501 with HAWC - Albert, Andrea; Abeysekara, A. U.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Baghmanyan, V.; et al. (Proceedings of Science, 2022)
HAWC has recently developed 2 new analysis techniques that reconstructs the energy of each gamma-ray event. With this new analysis HAWC has detected several Galactic sources with emission above 100 TeV. Additionally the HAWC Collaboration has developed new event reconstruction algorithms called “Pass 5”. Using the energy estimators and Pass 5 we search for >177 TeV emission in the vicinity of Mrk 501. High-energy emission from Mrk 501 could, for example, be evidence of Axion Like Particles, a theoretical dark matter candidate. We find a hint of a high-energy lobe within 0.5◦ of Mrk 501 using both energy estimators.
CRIS-Team Scopus Importer:2022-12-23

Searching for TeV Dark Matter in Irregular Dwarf Galaxies with HAWC Observatory - Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Rojas, D. Avila; Solares, H. A.Ayala; Babu, R.; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistrán, T.; Carramiñana, A.; Casanova, S.; Chaparro-Amaro, O.; et al. (Astrophysical Journal, 2023)
We present the results of dark matter (DM) searches in a sample of 31 dwarf irregular (dIrr) galaxies within the field of view of the HAWC Observatory. dIrr galaxies are DM-dominated objects in which astrophysical gamma-ray emission is estimated to be negligible with respect to the secondary gamma-ray flux expected by annihilation or decay of weakly interacting massive particles (WIMPs). While we do not see any statistically significant DM signal in dIrr galaxies, we present the exclusion limits (95% C.L.) for annihilation cross section and decay lifetime for WIMP candidates with masses between 1 and 100 TeV. Exclusion limits from dIrr galaxies are relevant and complementary to benchmark dwarf Spheroidal (dSph) galaxies. In fact, dIrr galaxies are targets kinematically different from benchmark dSph, preserving the footprints of different evolution histories. We compare the limits from dIrr galaxies to those from ultrafaint and classical dSph galaxies previously observed with HAWC. We find that the constraints are comparable to the limits from classical dSph galaxies and ∼2 orders of magnitude weaker than the ultrafaint dSph limits.
CRIS-Team Scopus Importer:2023-03-24

Spectral and Energy Morphology Analysis Study of HAWC J2031+415 - Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Baghmanyan, V.; et al. (Proceedings of Science, 2022)
The Cygnus Cocoon region is a complex region containing an OB star cluster that is prominent in the TeV energy range. Located in this region is 3HWC J2031+415, a significant TeV gamma-ray source whose emission is possibly associated with 2 components, the Cygnus OB2 star cluster and a pulsar wind nebula (PWN). In this work, several modelling methods are presented to best describe the emission. These models disentangle emission believed to be from the Cocoon and isolate the component emitted by the probable PWN. I will present several spectral models to describe the emission of the probable PWN using the latest data set from the High-Altitude Water Cherenkov (HAWC) observatory. Furthermore, I will present an energy morphology study of the PWN component of 3HWC J2031+415 in distinct energy bands.
CRIS-Team Scopus Importer:2024-12-16

Spectrum and morphology of the very-high-energy source HAWC J2019+368 - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Solares, H. A.Ayala; Baghmanyan, V.; Belmont-Moreno, E.; Brisbois, C.; Caballero-Mora, K. S.; Capistrán, T.; et al. (Astrophysical Journal, 2021)
The MGRO J2019+37 region is one of the brightest sources in the sky at TeV energies. It was detected in the second HAWC catalog as 2HWC J2019+367 and here we present a detailed study of this region using data from HAWC. This analysis resolves the region into two sources: HAWC J2019+368 and HAWC J2016+371. We associate HAWC J2016+371 with the evolved supernova remnant CTB 87, although its low significance in this analysis prevents a detailed study at this time. An investigation of the morphology (including possible energy-dependent morphology) and spectrum for HAWC J2019+368 is the focus of this work. We associate HAWC J2019+368 with PSR J2021+3651 and its X-ray pulsar wind nebula, the Dragonfly nebula. Modeling the spectrum measured by HAWC and Suzaku reveals a ∼7 kyr pulsar and nebula system producing the observed emission at X-ray and γ-ray energies.
CRIS-Team Scopus Importer:2021-05-21

Standardized Formats for Gamma-Ray Analysis Applied to HAWC Observatory Data - Olivera-Nieto, Laura; Joshi, Vikas; Schoorlemmer, Harm; Donath, Axel; Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; et al. (Proceedings of Science, 2022)
A wide range of data formats and proprietary software have traditionally been used in y-ray astronomy, usually developed for a single specific mission or experiment. However, in recent years there has been an increasing effort towards making astronomical data open and easily accessible. Within the y-ray community this has translated to the creation of a common data format across different y-ray observatories: the "gamma-astro-data-format" (GADF). Based on a similar premise, open-source analysis packages, such as Gammapy, are being developed and aim to provide a single, robust tool which suits the needs of many experiments at once. In this contribution we show that data from the High-Altitude Water Cherenkov (HAWC) observatory can be made compatible with the GADF and present the first GADF-based production of event lists and instrument response functions for a ground-based wide-field instrument. We use these data products to reproduce with excellent agreement the published HAWC Crab spectrum using Gammapy. Having a common data format and analysis tools facilitates joint analysis between different experiments and effective data sharing. This will be especially important for next-generation instruments, such as the proposed Southern Wide-field Gamma-ray Observatory (SWGO) and the planned Cherenkov Telescope Array (CTA).
CRIS-Team Scopus Importer:2024-12-16

Studying High-Mass Microquasars with HAWC - Hwang, Se Yeon; Son, Youngwan; Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; et al. (Proceedings of Science, 2022)
High-mass microquasars (HMMQs) are powerful particle accelerators, but their mechanism of the high-energy emission is poorly understood. To date, only a handful of these particle engines have ever been observed to emit gamma-ray photons and are thus potential TeV gamma-ray emitters. In this work, we study four HMMQs, namely, LS 5039, Cyg X-1, Cyg X-3, and SS 433 using the data from the High Altitude Water Cherenkov (HAWC) observatory. We perform time dependent analyses on each HMMQ to look for any periodic variations in their flux. We produce light curves using the HAWC daily maps from which we generate Lomb-Scargle periodograms. By analysing the significance of the periodogram peaks, we assess whether or not HAWC is sensitive to orbitally modulating TeV gamma-ray flux in the four HMMQs.
CRIS-Team Scopus Importer:2024-12-16

Study of the eHWC J1825-134 Region at Highest Energies with HWAC - Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Baghmanyan, V.; et al. (Proceedings of Science, 2022)
eHWC J1825-134 is one of the brightest Galactic γ-ray sources above 50 TeV observed by High Altitude Water Cherenkov γ-Ray Observatory (HAWC). Detailed morphological studies have revealed a new point-like source inside this region with a spectral energy distribution extending beyond 200 TeV without any cutoff. These very-high-energy γ rays emission can originate from leptonic or hadronic processes. The new point-like source is located in a region containing PWNe and a high density giant molecular cloud [MML2017]99. If the source emission is associated with the hadronic scenario the TeV γ rays may have been produced by cosmic rays colliding with ambient gas. If this were the case, eHWC J1825-134 is an indicator of the existence of a galactic PeVatron in the region that accelerates particles up to PeV energies.
CRIS-Team Scopus Importer:2024-12-16

Study of the morphology of the region surrounding eHWC J1850+001 - Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Baghmanyan, V.; et al. (Proceedings of Science, 2022)
Although at extreme energies (>50 TeV) γ-ray sources generally have large angular separations from one another as observed on Earth, at lower energies in the galactic plane this is often not the case. HAWC observes extended emission from the source eHWC J1850+001 exceeding 50 TeV, and at lower energies this region appears to consist of multiple sources of γ-ray emission. These include the 3HWC J1849+001 source but also two nearby H.E.S.S. sources observed in their Galactic Plane Survey. Therefore, a full description of the region requires a morphological study including the full energy range of HAWC data. Understanding the spatial features of the emission in this region is important to associate the sources observations at other wavelengths, which may point to hadronic or leptonic origins for the γ-ray emission. There are multiple pulsar wind nebulae and super nova remnant systems in the vicinity that may be responsible for the emission in this region, including the pulsar PSR J1849+001 and its pulsar wind nebula, which is a likely candidate for the >50 TeV energy emission seen by HAWC.
CRIS-Team Scopus Importer:2024-12-16

Study of the Very High Energy Emission of M87 through its Broadband Spectral Energy Distribution - Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Belmont-Moreno, E.; Capistrán, T.; Carramiñana, A.; Casanova, S.; Cotti, U.; Cotzomi, J.; Coutiño de León, S.; et al. (Astrophysical Journal, 2022)
The radio galaxy M87 is the central dominant galaxy of the Virgo Cluster. Very high-energy (VHE, ≳0.1 TeV) emission from M87 has been detected by imaging air Cherenkov telescopes. Recently, marginal evidence for VHE long-term emission has also been observed by the High Altitude Water Cherenkov Observatory, a gamma-ray and cosmic-ray detector array located in Puebla, Mexico. The mechanism that produces VHE emission in M87 remains unclear. This emission originates in its prominent jet, which has been spatially resolved from radio to X-rays. In this paper, we construct a spectral energy distribution from radio to gamma rays that is representative of the nonflaring activity of the source, and in order to explain the observed emission, we fit it with a lepto-hadronic emission model. We found that this model is able to explain nonflaring VHE emission of M87 as well as an orphan flare reported in 2005.
CRIS-Team Scopus Importer:2022-08-19

TeV Analysis of a Source-rich Region with the HAWC Observatory: Is HESS J1809-193 a Potential Hadronic PeVatron? - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Babu, R.; Belmont-Moreno, E.; Bernal, A.; Breuhaus, M.; Caballero-Mora, K. S.; Capistrán, T.; Carramiñana, A.; et al. (Astrophysical Journal, 2024)
HESS J1809-193 is an unidentified TeV source, first detected by the High Energy Stereoscopic System (H.E.S.S.) collaboration. The emission originates in a source-rich region that includes several supernova remnants (SNRs) and pulsars including SNR G11.1+0.1, SNR G11.0-0.0, and the young radio pulsar PSR J1809-1917. Originally classified as a pulsar wind nebula candidate, recent studies show the peak of the TeV region overlapping with a system of molecular clouds. This resulted in the revision of the original leptonic scenario to look for alternate hadronic scenarios. Marked as a potential PeVatron candidate, this region has been studied extensively by H.E.S.S. due to its emission extending up to several tens of TeV. In this work, we use 2398 days of data from the High Altitude Water Cherenkov (HAWC) observatory to carry out a systematic source search of the HESS J1809-193 region. We were able to resolve emission detected as an extended component (modelled as a symmetric Gaussian with a 1σ radius of 0.°21) with no clear cutoff at high energies and emitting photons up to 210 TeV. We model the multiwavelength observations for the region around HESS J1809-193 using a time-dependent leptonic model and a lepto-hadronic model. Our model indicates that both scenarios could explain the observed data within the region of HESS J1809-193.
CRIS-Team Scopus Importer:2024-09-13

The gamma-ray emission from 3HWC J1928+178 - Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Camacho, J. R.Angeles; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Baghmanyan, V.; et al. (Proceedings of Science, 2022)
The gamma-ray source 3HWC J1928+178, discovered by HAWC, is coincident with the 82 kyr pulsar PSR J1928+1746, located 4 kpc away. It has not been reported by any Imaging atmospheric Cherenkov Telescope (IACT), until the recent detection of emission from this region by HESS, using an analysis adapted to extended sources. No counterpart in GeV gamma-rays from Fermi-LAT data or in X-ray has been reported so far. In this contribution, I give the multiwavelength context of the region surrounding 3HWC J1928+178 and present a multi-component model derived using the Multi-Mission Maximum Likelihood framework (3ML). I explore the possibility to model the gamma-ray emission of 3HWC J1928+178 by an extended source with continuous diffuse emission. Together with the age of the pulsar and its extended nature, it may indicate a transition from a pulsar wind nebulae to a halo, where the electrons have started to cool and diffuse away from the source.
CRIS-Team Scopus Importer:2024-12-16

The High-Altitude Water Cherenkov (HAWC) observatory in México: The primary detector - Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Araya, M.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Solares, H. A.Ayala; Babu, R.; Barber, A. S.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2023)
The High-Altitude Water Cherenkov (HAWC) observatory is a second-generation continuously operated, wide field-of-view, TeV gamma-ray observatory. The HAWC observatory and its analysis techniques build on experience of the Milagro experiment in using ground-based water Cherenkov detectors for gamma-ray astronomy. HAWC is located on the Sierra Negra volcano in México at an elevation of 4100 meters above sea level. The completed HAWC observatory principal detector (HAWC) consists of 300 closely spaced water Cherenkov detectors, each equipped with four photomultiplier tubes to provide timing and charge information to reconstruct the extensive air shower energy and arrival direction. The HAWC observatory has been optimized to observe transient and steady emission from sources of gamma rays within an energy range from several hundred GeV to several hundred TeV. However, most of the air showers detected are initiated by cosmic rays, allowing studies of cosmic rays also to be performed. This paper describes the characteristics of the HAWC main array and its hardware.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Astrophysics; High energy physics — experiment; Nuclear experiment; Physics — instrumentation and detectors; Water Cherenkov Detectors

The Ultra-High-Energy Source MGRO J1908+06 - Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Baghmanyan, V.; et al. (Proceedings of Science, 2022)
The TeV gamma-ray source MGRO J1908+06 is one of the highest-energy sources known, with observed emission by the High Altitude Water Cherenkov (HAWC) Observatory extending well past 100 TeV. The source exhibits both energy-dependent morphology and a spatially-dependent spectral index. The emission is likely to be dominantly leptonic, and associated with the radio-quiet PSR J1907+0602. However, one-population models do not describe the data well; a second particle population is needed to explain the shape of the spectral energy distribution at the highest energies. This component can be well-described by either leptonic or hadronic hypotheses. We discuss this feature and implications for detection by multi-wavelength and multi-messenger experiments.
CRIS-Team Scopus Importer:2024-12-16

Ultra-high-energy gamma-ray bubble around microquasar V4641 Sgr - Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistrán, T.; Carramiñana, A.; Casanova, S.; Cotti, U.; et al. (Nature, 2024)
Microquasars are laboratories for the study of jets of relativistic particles produced by accretion onto a spinning black hole. Microquasars are near enough to allow detailed imaging of spatial features across the multiwavelength spectrum. The recent extension measurement of the spatial morphology of a microquasar, SS 433, to TeV gamma rays1 localizes the acceleration of electrons at shocks in the jet far from the black hole2. V4641 Sagittarii (V4641 Sgr) is a similar binary system with a black hole and B-type main-sequence companion star and has an orbit period of 2.8 days (refs. 3,4). It stands out for its super-Eddington accretion5 and for its radio jet, which is one of the fastest superluminal jets in the Milky Way. Previous observations of V4641 Sgr did not report gamma-ray emission6. Here we report TeV gamma-ray emission from V4641 Sgr that reveals particle acceleration at similar distances from the black hole as SS 433. Furthermore, the gamma-ray spectrum of V4641 Sgr is among the hardest TeV spectra observed from any known gamma-ray source and is detected above 200 TeV. Gamma rays are produced by particles, either electrons or protons, of higher energies. Because energetic electrons lose energy more quickly the higher their energy, such a spectrum either very strongly constrains the electron-production mechanism or points to the acceleration of high-energy protons. This suggests that large-scale jets from microquasars could be more common than previously expected and that they could be a notable source of galactic cosmic rays7–9.
CRIS-Team Scopus Importer:2024-10-25

Very high energy gamma-ray emission from two blazars of unknown redshift and upper limits on their distance - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; et al. (Monthly Notices of the Royal Astronomical Society, 2020)
We report on the detection of very high energy (VHE; E > 100 GeV) gamma-ray emission from the BL Lac objects KUV 00311-1938 and PKS 1440-389 with the High Energy Stereoscopic System (H.E.S.S.). H.E.S.S. observations were accompanied or preceded by multiwavelength observations with Fermi/LAT, XRT and UVOT onboard the Swift satellite, and ATOM. Based on an extrapolation of the Fermi/LAT spectrum towards the VHE gamma-ray regime, we deduce a 95 per cent confidence level upper limit on the unknown redshift of KUV 00311-1938 of z < 0.98 and of PKS 1440-389 of z < 0.53. When combined with previous spectroscopy results, the redshift of KUV 00311-1938 is constrained to 0.51 <= z < 0.98 and of PKS 1440-389 to 0.14 (sic) z < 0.53.
CRIS-Team WoS Importer:2020-06-26

γ-Ray Emission from Classical Nova V392 Per: Measurements from Fermi and HAWC - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Rojas, D. Avila; Solares, H. A.Ayala; Babu, R.; Belmont-Moreno, E.; Blochwitz, C.; Caballero-Mora, K. S.; Capistrán, T.; Carramiñana, A.; et al. (Astrophysical Journal, 2022)
This paper reports on the γ-ray properties of the 2018 Galactic nova V392 Per, spanning photon energies ∼0.1 GeV-100 TeV by combining observations from the Fermi Gamma-ray Space Telescope and the HAWC Observatory. As one of the most rapidly evolving γ-ray signals yet observed for a nova, GeV γ-rays with a power-law spectrum with an index Γ = 2.0 ± 0.1 were detected over 8 days following V392 Per’s optical maximum. HAWC observations constrain the TeV γ-ray signal during this time and also before and after. We observe no statistically significant evidence of TeV γ-ray emission from V392 Per, but present flux limits. Tests disfavor the extension of the Fermi Large Area Telescope spectrum to energies above 5 TeV by 2 standard deviations (95%) or more. We fit V392 Per’s GeV γ-rays with hadronic acceleration models, incorporating optical observations, and compare the calculations with HAWC limits.
CRIS-Team Scopus Importer:2022-12-23